Analysis of Marketing Strategies to Increase MSME Income (Case Study of STAMPAI MSME) - Ruhul Fitri Rosel; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
Indonesia is one of the countries with a large number of MSME sectors. The establishment of MSME is one solution that can overcome both economic problems and unemployment problems. The goal of this study is to learn about MSMEs' marketing strategies in order to help them boost their revenue. The study, planning, implementation, and supervision of programs aimed at developing exchanges with the target market with the goal of accomplishing business goals is referred to as marketing strategy. Marketing strategy is able to describe a series of activities in achieving predetermined goals. This type of research is descriptive qualitative. This research was conducted at the STAMPAI MSME which is located at Jl, Kurnia, Tiakar Village, Kec. East Payakumbuh, Payakumbuh City. By using a SWOT analysis, you can find out what kind of marketing strategy is the most effective. Internal factors such as strengths and weaknesses, as well as external factors such as opportunities and threats are considered by MSMEs. The marketing strategy applied to this MSME is the Marketing Mix which consists of 4Ps, namely product, price, place, and promotion.